2017
DOI: 10.1007/s00281-017-0629-x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic human coronavirus infections: causes and consequences of cytokine storm and immunopathology

Abstract: Human coronaviruses (hCoVs) can be divided into low pathogenic and highly pathogenic coronaviruses. The low pathogenic CoVs infect the upper respiratory tract and cause mild, cold-like respiratory illness. In contrast, highly pathogenic hCoVs such as severe acute respiratory syndrome CoV (SARS-CoV) and Middle East respiratory syndrome CoV (MERS-CoV) predominantly infect lower airways and cause fatal pneumonia. Severe pneumonia caused by pathogenic hCoVs is often associated with rapid virus replication, massive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

74
2,311
0
102

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 2,299 publications
(2,565 citation statements)
references
References 129 publications
74
2,311
0
102
Order By: Relevance
“…2 , 5 Previous studies indicated that viral evasion of host maladjusted immune responses are believed to play critical roles in acute lung injury (ALI), in addition to CoVs-induced direct cytopathic effects. 5 Indeed, changes of some immune index have been detected in the CoVs infection patients, such as lymphopenia, monocytosis and elevated cytokine levels. 2 , 5 , 25 The treatment of corticosteroids may reduce the risk of lung inflammation but also delay CoVs clearance in addition to other side effects.…”
Section: Discussionmentioning
confidence: 99%
“…2 , 5 Previous studies indicated that viral evasion of host maladjusted immune responses are believed to play critical roles in acute lung injury (ALI), in addition to CoVs-induced direct cytopathic effects. 5 Indeed, changes of some immune index have been detected in the CoVs infection patients, such as lymphopenia, monocytosis and elevated cytokine levels. 2 , 5 , 25 The treatment of corticosteroids may reduce the risk of lung inflammation but also delay CoVs clearance in addition to other side effects.…”
Section: Discussionmentioning
confidence: 99%
“…MERS-CoV pathogenesis reflects a balance between coronavirus-induced protective and pathogenic host immune responses and direct cytotoxic effects of the virus. 52 According to studies of patients infected with SARS-CoV and of mice and other animals infected experimentally with MERS-CoV, successful resolution of MERS and long-term protection from re-infection likely requires well coordinated innate and adaptive B-cell and T-cell responses. In patients with SARS, innate immune responses characterised by an extended period of cytokine secretion (eg, IFNα and IFNβ) was correlated with delayed antibody responses and poor management outcomes; this prolonged innate response has not yet been shown in patients infected with MERS-CoV.…”
Section: Protective and Deleterious Immune Responsesmentioning
confidence: 99%
“…According to the statistics provided by the World Health Organization (WHO) on June 10, 2019, a total of 2428 laboratory-confirmed cases of human MERS-CoV infection have been reported, with an estimated 838 deaths in 27 countries. The accumulated evidence suggested that MERS-CoV infections are characterized by high levels of systemic inflammatory cytokines/chemokines as well as immunopathology [4][5][6][7][8][9][10][11]. High inflammatory cytokines and chemokines levels have been strongly correlated with poor disease outcomes, immunopathology and massive infiltration of the immune inflammatory cells into the lungs [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…High inflammatory cytokines and chemokines levels have been strongly correlated with poor disease outcomes, immunopathology and massive infiltration of the immune inflammatory cells into the lungs [10,12]. Moreover, the stimulation of various cytokines, chemokines and innate immune cells has been associated with the appearance of cytokine storms, which occur during infections with pathogenic coronavirus (CoV) and influenza virus [6,13,14]. In addition, increased IL-8 (CXCL8) levels play a key role in acute SARS https://doi.org/10.1016/j.cyto.2019.154895 Received 10 June 2019; Received in revised form 14 October 2019; Accepted 17 October 2019 infection, viral bronchiolitis pathogenesis, severe immunopathology, and disease enhancement during respiratory syncytial virus (HRSV) infection [10,12,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%